2006
DOI: 10.1097/01.hjr.0000238396.42718.61
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical training on exercise capacity, gas exchange and N-terminal pro-brain natriuretic peptide levels in patients with chronic heart failure

Abstract: Physical training of moderate intensity significantly improves the exercise capacity and neurohormonal modulation in patients with chronic heart failure. This is associated with an alleviation of symptoms and improvement in quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 31 publications
7
58
0
1
Order By: Relevance
“…Berent et al (2009) reported that 4 weeks of moderate exercise reduced the NTproBNP level, independent of the left ventricular ejection fraction, and improved physical Wtness and blood lipid proWles. Physical training of moderate intensity signiWcantly improves exercise capacity and reduces the serum level of NT pro-BNP in patients with chronic heart failure (Maria Sarullo et al 2006). In addition, the blood NT-proBNP level of athletes was signiWcantly lower than that of sedentary controls (Lippi et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Berent et al (2009) reported that 4 weeks of moderate exercise reduced the NTproBNP level, independent of the left ventricular ejection fraction, and improved physical Wtness and blood lipid proWles. Physical training of moderate intensity signiWcantly improves exercise capacity and reduces the serum level of NT pro-BNP in patients with chronic heart failure (Maria Sarullo et al 2006). In addition, the blood NT-proBNP level of athletes was signiWcantly lower than that of sedentary controls (Lippi et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…CR with ET has been shown to reduce BNP level; 12,13) however, it has remained unclear whether CR reduces ACR in patients with CVD. Supervised exercise training: Total exercise time was significantly longer in the supervised group than in the non-supervised group.…”
Section: Discussionmentioning
confidence: 99%
“…This study also demonstrated that early EP could increase physical fitness and could improve QoL within the first month. However, to decrease NT-proBNP level significantly, we probably need a longer period of exercise training, of at least 1.5 months [19].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training studies that recruited clinically stable, chronic patients with HF were generally considered to be safe, [4] and to decrease the NT-proBNP level, [19] but there was also a study that demonstrated an improvement in fitness level but did change the NTproBNP level, although the exercise training was conducted for 18 weeks [20]. In this study, there was a trend of decreasing the NTproBNP level by EP, but this was not statistically significant, probably due to the short duration of exercise training.…”
Section: Discussionmentioning
confidence: 99%